Pengaruh Indeks Produksi Industri, Suku Bunga BI Rate dan Capital Adequacy Ratio Terhadap Non Performing Loan pada Industri Perbankan Indonesia Periode 2017–2024 - Adam Ramadan Harahap; Harya Kuncara Wiralaga; Karuniana Dianta Arfiando Sebayang (Indo Publishing, 2026)
This study aims to analyze the effect of the Industrial Production Index (IPI), BI Rate, and Capital Adequacy Ratio (CAR) on Non-Performing Loans (NPL) in the Indonesian banking sector during the period 2017–2024. NPL is one of the key indicators used to assess credit quality and the stability of the banking sector. An increase in the NPL ratio may elevate systemic risk and potentially disrupt overall financial system stability. Changes in macroeconomic conditions and internal banking factors are assumed to play a role in influencing the level of NPL; therefore, empirical analysis is required to better understand these relationships.This study employs a quantitative approach using monthly time series data obtained from official publications of Bank Indonesia, Statistics Indonesia (BPS), the Financial Services Authority (OJK), and CEIC Data. The analytical method used is multiple linear regression with the assistance of SPSS software. Prior to model estimation, the data were tested using descriptive statistics, stationarity tests, classical assumption tests, and outlier treatment to ensure the validity and reliability of the model. The results indicate that the Industrial Production Index (IPI) has a positive but insignificant effect on NPL. Meanwhile, the BI Rate has a negative and significant effect on NPL, indicating that interest rate policy is associated with banking credit quality. In addition, the Capital Adequacy Ratio (CAR) is found to have a positive and significant effect on NPL, suggesting that higher bank capital is associated with increased exposure to credit risk. Based on these findings, it can be concluded that external factors such as monetary policy and internal banking factors play a role in influencing NPL, although not all variables show a significant effect. However, simultaneously, the three variables have a significant effect on NPL. This study is expected to contribute to the development of literature in the banking sector and serve as a reference for relevant stakeholders in maintaining financial system stability.